A Study on Seroprevalence among Clinically Suspected Dengue Viral Infection using IgM Antibody Capture ELISA for the Early Diagnosis - C, Dr. Prabhurajeshwar (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
Background: Dengue is an acute viral illness caused by RNA virus of the family Flaviviridae and spread by Aedes mosquitoes occur mainly in four closely related serotypes (DENV1-4). It has developed into emergent threat in the India and Karnataka state now. Karnataka state now and also challenges associated with patient administration in dengue infection is early diagnosis. Objective: The objective of the study was to determine the prevalence of dengue infection in the Kalaburagi district by serological test IgM enzyme-linked immunosorbent assay (ELISA). The detection of immunoglobulin (Ig)M is the core method for the laboratory diagnosis of dengue. The present study considered the relevance of a rapid test for dengue pertaining to new cases and assessment of the epidemic attack rate. Methods: This evocative study was conducted at our Gulbarga Institute of Medical Sciences Hospital, Kalaburagi, for the period between January and December 2018. Serum samples were collected from suspected dengue patients attended in- and out-patient department, a detailed history and full clinical assessment was done. Sera were analyzed by capture ELISA for the presence of dengue IgM antibodies. Results: Over the study period, out of 1807 samples, 123 were showed positive for dengue virus infection (14.69%). Both male 61 (49.59%) and female 62 (50.40%) patients predominantly affected equally. The positive peak values were noticed between the month of April and December 2018. The most positivity was observed in the age group of 1–20 years. Among these tests, the National Institute of Virology (NIV, ICMR) kit has shown to have an overall sensitivity of 81.6% and a specificity of 97.9–99%. Conclusion: The present results revealed that the study region is both epidemic and endemic for dengue viral infection and there is an urgent need for the constant monitoring to control further spreading of the infection in the community, hence, serological test has an important role in the early diagnosis. Therefore, IgM ELISA is recommended in all the suspected dengue patients so as to diagnose early, instigate essential treatment, and assessment of morbidity and mortality rate during an outbreak.